Trend analysis of climatic variables in Betwa river basin - DESAI, SUJEET; SINGH, D K; ISLAM, ADLUL; SARANGI, A; KHANNA, MANOJ (The Indian Journal of Agricultural Sciences, 2019)
A study was undertaken to establish the annual trend in climatic variables of the Betwa basin located in Central India. District wise daily data (1971–2007) of rainfall, maximum and minimum temperature, relative humidity and wind speed were analysed using Mann-Kendall test and Sen’s slope estimator. The annual rainfall in majority of the districts showed non-significant decreasing trend. Maximum temperature exhibited significant increasing trend in nine out of 14 districts, whereas minimum temperature exhibited significant increasing trend in only four districts. Relative humidity has increased significantly in Bhopal and Jhansi districts, whereas wind speed has significantly decreased in Bhopal, Jhansi, Tikamgarh and Vidisha districts. Decrease in the rainfall varied from 0.674 to 6.46 mm/year which was insignificant. The increase in mean daily maximum and minimum temperature varied from 0.014–0.022°C/year and 0.015–0.024°C/year, respectively. Significant increase in relative humidity was in the range of 0.18–0.34% per year, whereas decrease in the wind speed varied from -0.053 to -0.186 km/h/year. Results of the trend analysis indicated spatial variability in the changes in the different climatic variables.These results will be useful for planning appropriate water management strategies, agricultural crop planning, and preparing location specific adaptation measures.